Kajian Pengaruh Jenis dan Komposisi Bahan Perekat Organik terhadap Kualitas Briket Batubara Sub-bituminus di Pabrik Briket PT Bukit Asam (Persero) Tbk. - Ignatius William Yudha; Maulana Yusuf; Muhammad Rendana (Dinasti Research, 2026)
This study examines the effect of the type and composition of organic binders on the quality of sub-bituminous coal briquettes at the PT Bukit Asam Tbk Briquette Factory. The innovation focuses on utilizing palm oil industry liquid waste in the form of Palm Oil Mill Effluent (POME) sludge as a natural thermoplastic binder, which is directly compared with a commercial food-based binder (tapioca). The tests were conducted using varying POME sludge substitution percentages (0%, 1.7%, 3.3%, and 5%), with a primary focus on the thermal and proximate characteristics. The results showed that POME sludge acts as a calory booster, linearly increasing the gross calorific value (GCV) of the briquettes from 5,909 kcal/kg to 6,330 kcal/kg (adb) due to the high hydrocarbon density of palm lipids. Proximate analysis confirmed a decrease in inherent moisture (from 5.33% to 4.17%) due to the hydrophobic nature of the lipids, alongside an increase in volatile matter (from 15.20% to 17.67%) and a moderate increase in ash content from 12.87% to 14.70%. Fixed carbon decreased from 64.87% to 61.28% with the increase of the palm phase, while the total sulfur content remained in a very low and safe category (maximum 0.26%). This palm phase substitution successfully enhanced the energy density of low-rank coal briquettes significantly.